Redox state and metabolic responses to severe heat stress in lenok Brachymystax lenok (Salmonidae) - Chen, Yan; Pan, Zhe; Bai, Yucen; Xu, Shaogang (Frontiers in Molecular Biosciences, 2023)
Dynamic changes in redox state and metabolic responses are studied in lenok (Brachymystax lenok: Salmonidae) exposed to acute and severe heat stress (25°C, 48 h). Nicotinamide adenine dinucleotide (NAD+) consumption causes significant increases in ratio of reduced NADH to NAD+ and ratio of reduced nicotinamide adenine dinucleotide phosphate (NADPH) to NADP+, which induced oxidative stress via generation of reactive oxygen species. Lowered reduced glutathione/oxidized glutathione (GSH/GSSG) ratios suggest that more oxidized conditions occur in heat-stressed lenok, leading to membrane lipid oxidation. The first few hours of heat stress promote the activity of enzymes involved in anaerobic glycolysis (hexokinase, pyruvate kinase, lactic dehydrogenase) and glutamic-pyruvic transaminase and glutamic oxaloacetic transaminase, which may lead to consumption of many carbohydrates and amino acid catabolism. Enzyme activities decrease with time in a possible compensatory strategy to manage reactive oxygen species production and oxidative stress. After 48 h of recovery, NAD+, carbohydrate levels and enzyme activities had returned to control levels, whereas many amino acids were consumed for repair and new synthesis. GSH remained at levels lower than controls, and the more oxidized conditions had not recovered, aggravating oxidative damage. Glutamic acid, glutamine, lysine and arginine may play important roles in survival of heat-stressed lenok.